Electrophotographic photoreceptor, image forming apparatus equipped with same, method for producing electrophotographic photoreceptor, and coating liquid for charge transport layer used therein

JP7633915B2Active Publication Date: 2025-02-20SHARP KK
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021151371
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-16
Publication Date
2025-02-20
Estimated Expiration
2041-09-16

Smart Images

  • Figure 0007633915000013
    Figure 0007633915000013
  • Figure 0007633915000014
    Figure 0007633915000014
  • Figure 0007633915000015
    Figure 0007633915000015
Patent Text Reader

Abstract

To provide an electro-photographic photoreceptor which has the excellent printing durability and high mechanical strength and does not cause image density unevenness, an image formation apparatus having the same, a manufacturing method of the electro-photographic photoreceptor, and a coating liquid for charge transfer layer used for the same.SOLUTION: An electro-photographic photoreceptor includes at least a lamination type photosensitive layer in which a charge generation layer and a charge transfer layer are laminated in this order on a conductive support body. The charge transfer layer contains at least a charge transfer material, a binder resin and silica particles, and contains Na elements being equal to or greater than 0.1 ppm and equal to or less than 20 ppm and / or K elements being equal to or greater 0.01 ppm and equal to or less than 10 ppm.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrophotographic photoreceptor, an image forming apparatus having the same, a method for producing the electrophotographic photoreceptor, and a coating liquid for a charge transport layer used therein. More specifically, the present invention relates to an electrophotographic photoreceptor having excellent printing durability, high mechanical strength, and no image density unevenness, an image forming apparatus having the same, a method for producing the electrophotographic photoreceptor, and a coating liquid for a charge transport layer used therein. [Background technology]

[0002] In recent years, organic photoreceptors using organic photoconductive materials (herein referred to as "electrophotographic photoreceptors" or simply "photoreceptors") have been widely used as electrophotographic photoreceptors. However, organic photoreceptors have a drawback in that their surfaces are easily worn away by the friction of a cleaning blade or the like around the photoreceptor due to the nature of the organic materials used. On the other hand, in recent years, with an increase in contact charging methods using roller charging and with the trend toward longer life, smaller size and higher speed of electrophotographic devices such as digital copiers and printers, the surface of the organic photoreceptor is more susceptible to wear and is exposed to even harsher conditions. As a means for overcoming the above-mentioned drawbacks, efforts have been made up to now to improve the mechanical properties (wear resistance, printing durability) of the material surface of the photoreceptor.

[0003] Specifically, the addition of inorganic fine particles such as silica or alumina (also simply referred to as "inorganic particles") as a filler to the outermost surface layer of the photoreceptor has been considered. Also under consideration is a method of forming a curable protective layer (also called a "surface protective layer") on the charge transport layer and adding inorganic fine particles such as silica particles as a filler to the outermost surface layer. Furthermore, Japanese Patent Laid-Open Publication No. 9-211873 (Patent Document 1) discloses a method for producing a coating liquid for producing an electrophotographic photoconductor by dispersing pigment particles for the electrophotographic photoconductor together with a binder in a solvent, the method comprising the step of: dispersing the pigment particles for the electrophotographic photoconductor together with a binder in a solvent; and the method for producing a coating liquid for producing an electrophotographic photoconductor, the dispersing medium for dispersing the pigment particles for the electrophotographic photoconductor being at least one dispersing medium selected from soda glass beads, low-alkali glass beads, and yttria-containing zirconia beads; and an electrophotographic photoconductor having a charge generation layer formed using the coating liquid. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 9-211873 Summary of the Invention [Problem to be solved by the invention]

[0005] However, in the above-mentioned prior art, it is difficult to simultaneously improve the abrasion resistance of the photoreceptor surface and maintain stable image characteristics over a long period of time. Therefore, an object of the present invention is to provide an electrophotographic photoreceptor which has excellent printing durability, high mechanical strength and does not cause uneven image density, an image forming apparatus including the same, a method for producing an electrophotographic photoreceptor, and a coating liquid for a charge transport layer used therein. [Means for solving the problem]

[0006] As a result of intensive research into solving the above-mentioned problems, the inventors have discovered that a photoreceptor comprising at least a laminated photosensitive layer in which a charge generating layer and a charge transport layer are laminated in this order on a conductive support, in which the charge transport layer contains a specific amount of Na element and / or K element, has a good dispersion state of silica particles in the charge transport layer and can solve the above-mentioned problems, thereby completing the present invention.

[0007] Thus, according to the present invention, there is provided a photosensitive layer having a charge generating layer and a charge transport layer laminated in this order on a conductive support, The charge transport layer contains at least a charge transport material, a binder resin and silica particles, and also contains 0.1 ppm to 20 ppm of Na element and / or 0.01 ppm to 10 ppm of K element.

[0008] According to the present invention, there is also provided an image forming apparatus comprising at least the above-mentioned electrophotographic photosensitive member, charging means for charging the electrophotographic photosensitive member, exposure means for exposing the charged electrophotographic photosensitive member to light to form an electrostatic latent image, developing means for developing the electrostatic latent image formed by exposure to form a toner image, transfer means for transferring the toner image formed by development onto a recording medium, fixing means for fixing the transferred toner image on the recording medium to form an image, cleaning means for removing and recovering toner remaining on the electrophotographic photosensitive member, and discharging means for discharging surface charge remaining on the electrophotographic photosensitive member.

[0009] Further, according to the present invention, there is provided a method for producing the above electrophotographic photoreceptor, The present invention provides a method for producing an electrophotographic photoreceptor, comprising the step of forming a charge transport layer using a coating liquid for the charge transport layer, the coating liquid containing at least a charge transport material, a binder resin, and silica particles, and containing 0.1 ppm or more and 20 ppm or less of Na element and / or 0.01 ppm or more and 10 ppm or less of K element based on the solid content.

[0010] According to the present invention, there is also provided a coating liquid for a charge transport layer, which is used in the above-mentioned method for producing an electrophotographic photoreceptor, The present invention provides a coating liquid for a charge transport layer, which contains at least a charge transport material, a binder resin, and silica particles, and contains 0.1 ppm to 20 ppm of Na element and / or 0.01 ppm to 10 ppm of K element based on the solid content. Effect of the Invention

[0011] According to the present invention, it is possible to provide an electrophotographic photoreceptor having excellent printing durability, high mechanical strength, and no unevenness in image density, and an image forming apparatus equipped with the same. [Brief description of the drawings]

[0012] [Figure 1] 1 is a schematic cross-sectional view showing the configuration of a main part of a photoreceptor 1 of the present invention. [Diagram 2] 1 is a schematic cross-sectional view showing the configuration of a main part of a photoreceptor 2 of the present invention. [Diagram 3] 1 is a schematic side view illustrating a configuration of a main part of an image forming apparatus according to the present invention. [Figure 4] 1 is a scanning transmission electron microscope image showing the dispersion state of silica particles on the surface of the charge transport layer of the photoreceptor of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The photoreceptor of the present invention realizes both improved wear resistance of the photoreceptor surface and stable image characteristics over a long period of time, which was difficult to achieve with the prior art. That is, in the prior art, when the dispersion of inorganic fine particles becomes non-uniform in the outermost surface layer of the photoconductor, the mechanical strength of the part where the inorganic fine particles are localized and the part where the binder resin is present differs as the cleaning blade repeatedly scrapes off the remaining toner, so that the surface roughness of the photoconductor gradually increases as image formation is repeated, and the partial load on the cleaning blade increases, causing damage. Also, there is a problem that stable image characteristics cannot be obtained for a long time, such as uneven wear of the outermost surface layer causing color unevenness in the image.

[0014] The photoreceptor of the present invention has solved the above problems. That is, in the photoreceptor of the present invention, as shown in FIG. 4, the formation of aggregates of the silica particles added to the charge transport layer, which is the outermost surface layer, in order to improve the printing durability of the photoreceptor is suppressed, and the silica particles are uniformly dispersed in the charge transport layer, forming loose aggregate structures called "islands" (black parts in the figure) that resemble a uniform knitted structure in which the silica particles are interconnected in a "sea" of binder resin (white parts in the figure), thereby appearing to exhibit the excellent effects of the present invention as described above. In other words, by having the above-mentioned configuration, it is believed that a photoreceptor can be provided in which the variation in mechanical strength of the outermost charge transport layer is eliminated, the load on the blade is equalized, the progression of abrasive wear is suppressed, and the printing durability is significantly improved and partial damage to the cleaning blade is improved compared to conventional photoreceptors.

[0015] The present inventors conducted extensive research to optimize the dispersibility of silica particles in a coating solution for forming a constituent layer of a photoreceptor, and discovered that the dispersibility and uniformity of silica particles in the layer formed can be improved by contacting the coating solution mixture with a soda-lime glass material in the coating solution preparation process. Therefore, the dispersibility of silica in the coating solution and its effect were also examined for glass materials other than soda-lime glass (borosilicate glass, quartz glass) and metal materials, but it was found that the same effect could not be obtained. After further intensive research, they discovered that soda-lime glass materials have weaker mechanical strength than other materials, and that during the preparation process of the coating solution, the soda-lime glass material gradually wears away when it comes into contact with nanoparticle-sized silica particles, resulting in minute amounts of wear powder being mixed into the coating solution.

[0016] Therefore, the inventors assumed that since the soda-lime glass material contains metal oxides with high triboelectric charging properties such as sodium oxide, potassium oxide, calcium oxide, magnesium oxide, and aluminum oxide as constituent components, when the coating solution contains wear powder of these metal oxides, the silica particles in the coating solution are charged, and the wear powder is adsorbed on the surface of the silica particles, chemically modifying the surface of the silica particles and improving the dispersibility of the silica particles in the coating solution, and further verified this. As a result, among the constituent components of soda-lime glass, it was found that sodium oxide and potassium oxide, which have the second highest content ratio after silicon oxide, are contained in a larger amount in the wear powder compared to other elements. Therefore, when examining the analysis of the wear powder mixed in the coating liquid and the physical property values of the coating liquid, it was found that the sodium component and potassium component with high triboelectric charging properties of metal oxides greatly contribute to the dispersion stability of the silica particles, and the present invention was thus completed. The inventors believe that due to the large difference in electronegativity between oxygen atoms of sodium and potassium, a repulsive force acts between the silica particles by contacting and adsorbing on the surface of the silica particles, improving the dispersibility.

[0017] (1) Electrophotographic photoreceptor The photoreceptor of the present invention at least includes a laminated photosensitive layer in which a charge generation layer and a charge transport layer are laminated in this order on a conductive support. The charge transport layer contains at least a charge transport material, a binder resin, and silica particles, and is characterized by containing 0.1 ppm or more and 20 ppm or less of Na element and / or 0.01 ppm or more and 10 ppm or less of K element. First, the specific elements contained in the charge transport layer (Na element and K element, Ca element and Mg element described later), silica particles, and the content ratio of the specific elements and silica particles will be described, and then each component of the photoreceptor, (2) image forming apparatus, (3) manufacturing method of the electrophotographic photoreceptor, and (4) coating solution for the charge transport layer used therein will be described.

[0018] <Na element and K element> The photoreceptor of the present invention has a charge transport layer containing 0.1 ppm or more and 20 ppm or less of Na element and / or 0.01 ppm or more and 10 ppm or less of K element. If the content of the Na element is less than 0.1 ppm and the content of the K element is less than 0.01 ppm, almost no contribution to the dispersion stability of the silica particles can be obtained. On the other hand, if the content of the Na element exceeds 20 ppm and the content of the K element exceeds 10 ppm, although the dispersibility of the silica particles is good, when the charge is transported within the surface layer, the worn portion becomes a charge trap site and the charge movement is inhibited, which may lead to a deterioration in sensitivity. The content of the Na element is preferably 0.1 ppm or more and 10 ppm or less, and particularly preferably 0.1 ppm or more and 1.5 ppm or less. Also, the content of the K element is preferably 0.01 ppm or more and 2 ppm or less, and particularly preferably 0.01 ppm or more and 0.5 ppm or less. Regarding the content of the Na element, the K element, the Ca element, and the Mg element described below, for example, the charge transport layer of the photoreceptor can be measured using an ICP emission spectroscopic analyzer (manufactured by Thermo Fisher Scientific, model: iCAP-6500).

[0019] <Ca element and Mg element> The charge transport layer preferably contains 0.01 ppm or more and 10 ppm or less of Ca element and / or 0.01 ppm or more and 8 ppm or less of Mg element. Although the difference in electronegativity between oxygen of Ca and Mg is inferior to that of Na and K, they have an effect on the dispersion stability of the silica particles. If the content of the Ca element or the Mg element is less than 0.01 ppm, almost no contribution to the dispersion stability of the silica particles can be obtained. On the other hand, if the content of the Ca element exceeds 10 ppm and the content of the Mg element exceeds 8 ppm, although the dispersibility of the silica particles is good, when the charge is transported within the surface layer, the worn portion becomes a charge trap site and the charge movement is inhibited, which may lead to a deterioration in sensitivity. The content of the Ca element is more preferably 0.01 ppm or more and 1 ppm or less, and particularly preferably 0.01 ppm or more and 0.2 ppm or less. The content of Mg element is more preferably 0.01 ppm or more and 0.8 ppm or less, and particularly preferably 0.01 ppm or more and 0.2 ppm or less.

[0020] <Ratio of silica particles to Na element> The mass ratio [Na / SF] of the content of Na element [Na] to the content of silica particles [SF] in the charge transport layer is 8 × 10 -6 More than 2×10 -5 It is preferable that: If the content falls below the lower limit, the effect of improving the dispersibility of silica due to wear powder of each element cannot be obtained, the ten-point surface roughness Rz of the photoconductor increases, the load on the contact members increases, and problems such as blade chipping may occur. On the other hand, if the content exceeds the upper limit, the dispersibility of silica improves and the ten-point surface roughness Rz of the photoconductor decreases, but the number of trap sites for hole transport increases in the photosensitive layer, which may cause long-term adverse effects on image characteristics such as an increase in residual potential and deterioration of sensitivity. The mass ratio [Na / SF] is 1×10 -5 More than 2×10 -5 Less than or equal to 1×10 is preferable. -5 More than 1.7 x 10 -5 The following are particularly preferred:

[0021] <Ratio of silica particles to Ca elements> The mass ratio [Ca / SF] of the calcium element content [Ca] to the silica particle content [SF] in the charge transport layer is 1×10 -7 More than 1×10 -6 It is preferable that: If the content falls below the lower limit, the effect of improving the dispersibility of silica due to wear powder of each element cannot be obtained, the ten-point surface roughness Rz of the photoconductor increases, the load on the contact members increases, and problems such as blade chipping may occur. On the other hand, if the content exceeds the upper limit, the dispersibility of silica improves and the ten-point surface roughness Rz of the photoconductor decreases, but the number of trap sites for hole transport increases in the photosensitive layer, which may cause long-term adverse effects on image characteristics such as an increase in residual potential and deterioration of sensitivity. The mass ratio [Ca / SF] is 1×10 -7 5×10 or more-7 Less than or equal to 1×10 is preferable. -7 More than 2×10 -7 The following are particularly preferred:

[0022] <Silica particles> The photoreceptor of the present invention contains silica (silicon dioxide: SiO2) particles as a filler in the charge transport layer which is the outermost layer. Silica particles that can be suitably used in the present invention are not limited by the method of origin, and examples of the silica particles include dry process silica particles such as fumed silica obtained by burning silicon tetrachloride and arc process silica in which silica is atomized in the gas phase by high energy such as plasma; wet process silica particles such as precipitation process silica synthesized under alkaline conditions using an aqueous sodium silicate solution as a raw material and gel process silica synthesized under acidic conditions; colloidal silica particles obtained by polymerizing acidic silicic acid in an alkaline state; and sol-gel process silica particles obtained by hydrolysis of an organic silane compound.

[0023] <Number average primary particle size of silica particles> The silica particles preferably have a number average primary particle size of 10 nm or more and 30 nm or less. If the number average primary particle size of the silica particles is less than 10 nm, sufficient printing durability may not be obtained, whereas if the number average primary particle size of the silica particles is more than 30 nm, the aggregate structure formed in the photosensitive layer becomes large, which may easily cause problems such as poor cleaning. The number average primary particle size of the inorganic compound fine particles is more preferably 15 nm or more and 30 nm or less. The number average primary particle diameter can be calculated as the Feret's direction average diameter by observing silica particles under a scanning electron microscope at a magnification of 30,000 to 300,000 times, for example 100,000 times, randomly observing 100 particles as primary particles, and analyzing the image.

[0024] <Silica particle content> The content of silica particles as a filler is preferably 7% by mass or more and 18% by mass or less in the charge transport layer which is the outermost layer of the photoreceptor, and the silica particles are preferably uniformly dispersed. If the content of silica particles is less than 7% by mass, the effect on abrasion resistance may not be sufficient, whereas if the content of inorganic compound fine particles is more than 25% by mass, dispersibility may be insufficient, resulting in an increase in agglomerates and a deterioration in cleaning properties. The content of the inorganic compound fine particles in the outermost layer is more preferably from 7% by mass to 15% by mass, and particularly preferably from 8% by mass to 13% by mass.

[0025] <Surface treatment of inorganic compound particles> The silica particles are preferably surface-treated with a surface treatment agent in order to improve the electrical properties of the photoreceptor. When the inorganic compound fine particles are silica particles, examples of the surface treatment agent include hexamethyldisilazane, N-methyl-hexamethyldisilazane, N-ethyl-hexamethyldisilazane, hexamethyl-N-propyldisilazane, dimethyldichlorosilane, and polydimethylsiloxane. Among these surface treatment agents, dimethyldichlorosilane and hexamethyldisilazane are particularly preferred because they have good reactivity with the hydroxyl groups on the silica particle surface, reducing the number of hydroxyl groups on the silica particle surface, and as a result, can suppress the deterioration of the electrical properties of the photoreceptor due to moisture (humidity).

[0026] In the present invention, the silica particles obtained by treating with the above-mentioned surface treatment agent can be used, but commercially available silica fine particles treated with a surface treatment agent can also be used. Examples of commercially available silica fine particles include Nippon Aerosil Co., Ltd.'s product names: R972, R974, RX50, RX200, NX130, NX90G, NX90S, NAX-50; Cabot Japan Co., Ltd.'s product names: TS610, TG709F, TG6110G; and Admatechs Co., Ltd.'s product name: YA010C.

[0027] <Surface roughness Rz of charge transport layer> The charge transport layer of the photoreceptor of the present invention preferably has a ten-point surface roughness Rz of 0.1 μm or more and 1.0 μm or less, as defined by JIS-B-0601 (1994). This is achieved by appropriately and uniformly agglomerating inorganic compound fine particles having a small particle size. Generally, the larger the particle size of the inorganic compound fine particles, the higher the abrasion resistance, but this causes chipping of the edge of the cleaning blade. In the present invention, by appropriately agglomerating small inorganic compound fine particles, large particles are created, improving the abrasion resistance, and in the case of chipping of the cleaning blade, the small particles peel off, making it difficult for partial damage to occur.

[0028] Surface roughness Rz is an index of the state of aggregation of silica particles in the charge transport layer of a photoreceptor, and the ten-point average roughness Rz defined in JIS-B-0601 (1994) means the difference, expressed in μm, between the average elevations of the five highest peaks and the average elevations of the five deepest valleys measured in a reference length taken from the cross-sectional curve of the outermost surface layer of the photoreceptor, in a direction perpendicular to the average line from a straight line that is parallel to the average line and does not cross the cross-sectional curve, and the measurement method will be described in the examples.

[0029] If the surface roughness Rz is less than 0.1 μm, the interaction between the silica particles is insufficient and it is difficult to obtain the effect of wear resistance.On the other hand, if the surface roughness Rz exceeds 1.0 μm, the silica particles will aggregate too much, which may easily cause a state in which part of the edge of the cleaning blade is chipped, making it impossible to sufficiently clean the remaining toner, and may cause streak-like defects in the printed image. The surface roughness Rz is more preferably from 0.2 μm to 0.5 μm, and particularly preferably from 0.2 μm to 0.35 μm.

[0030] <Photoconductor> The photoreceptor of the present invention comprises at least a laminated photosensitive layer in which a charge generating layer and a charge transport layer are laminated in this order on a conductive support, and the charge transport layer contains at least a charge transport material, a binder resin and silica particles. The outermost layer is a charge transport layer constituting a laminated photosensitive layer, and the charge transport layer may be a single layer or a two-layer structure of a first charge transport layer and a second charge transport layer laminated in sequence on a charge generating layer. In the case of a two-layer structure, it is preferable that the first charge transport layer contains a charge transport material and a binder resin, and the second charge transport layer, which is the outermost layer, contains a charge transport material, a binder resin, and silica particles. The photoreceptor of the present invention, in which the outermost layer is a charge transport layer, will be described below with reference to the drawings, but the present invention is not limited thereto.

[0031] FIG. 1 is a schematic cross-sectional view showing the configuration of a main part of a photoreceptor 1 of the present invention. The photoreceptor 1 is a laminated photoreceptor (also referred to as a "function-separated photoreceptor") in which an undercoat layer 12 is provided on a conductive support 11, and a laminated photosensitive layer (also referred to as a "function-separated laminated photosensitive layer") 17 having a laminated structure in which a charge generation layer 13 containing a charge generation substance (not shown), a charge transport substance (not shown), a binder resin (not shown) that binds the charge transport substance, and a charge transport layer 14 containing silica particles 18 are laminated in this order. FIG. 2 is a schematic cross-sectional view showing the configuration of a main part of a photoreceptor 2 of the present invention. Photoreceptor 2 is a two-layer structure consisting of a first charge transport layer 15 and a second charge transport layer 16, which are successively stacked on a charge generating layer of the single charge transport layer 14 of photoreceptor 1, and has the same configuration as photoreceptor 1 except that second charge transport layer 16 contains silica particles 18. Each component of the photoreceptor 1 will now be described.

[0032] <Conductive support 11> The conductive support has a function as an electrode for the photoreceptor and a function as a support member, and the material constituting the conductive support is not particularly limited as long as it is a material used in the relevant technical field. Specific examples include metal materials such as aluminum, aluminum alloys, copper, zinc, stainless steel, and titanium, as well as polymer materials such as polyethylene terephthalate, nylon, and polystyrene, whose surfaces are laminated with metal foil, subjected to metal vapor deposition, or vapor-deposited or coated with a layer of a conductive compound such as a conductive polymer, tin oxide, or indium oxide, as well as hard paper and glass. Among these, aluminum is preferred from the viewpoint of ease of processing, and aluminum alloys such as JIS 3003, JIS 5000, and JIS 6000 are particularly preferred. The shape of the conductive support is not limited to a cylindrical shape (drum shape) as shown in FIG. 3, but may be a sheet shape, a columnar shape, an endless belt shape, or the like. In addition, the surface of the conductive support may be subjected to anodizing film treatment, surface treatment with chemicals or hot water, coloring treatment, or diffuse reflection treatment such as surface roughening, as necessary, to prevent interference fringes caused by laser light, within a range that does not affect image quality.

[0033] <Undercoat layer (also called "middle layer") 12> The photoreceptor of the present invention preferably includes an undercoat layer 12 between the conductive support 11 and the laminated type photosensitive layer 17 . The undercoat layer generally covers the unevenness of the surface of the conductive support to make it uniform, improves the film-forming property of the laminated photosensitive layer, here the charge generating layer, suppresses peeling of the laminated photosensitive layer from the conductive support, and improves the adhesion between the conductive support and the laminated photosensitive layer. Specifically, it prevents the injection of charge from the conductive support into the laminated photosensitive layer, prevents a decrease in the chargeability of the laminated photosensitive layer, and prevents image fogging (so-called black spots), and maintains good electrophotographic properties such as chargeability throughout the life of the electrophotographic film.

[0034] The undercoat layer can be formed, for example, by dissolving a binder resin in a suitable solvent to prepare a coating liquid for the undercoat layer, coating this coating liquid on the surface of the conductive support, and removing the organic solvent by drying.

[0035] Examples of the binder resin include the same binder resin as that contained in the laminated photosensitive layer described later, as well as natural polymeric materials such as casein, gelatin, polyvinyl alcohol, and ethyl cellulose, and one or more of these can be used. The binder resin is required to have properties such as not dissolving or swelling in the solvent used when forming the photoreceptor layer on the undercoat layer, excellent adhesion to the conductive support, and flexibility. Therefore, among the above-mentioned binder resins, polyamide resins are preferred, and alcohol-soluble nylon resins are particularly preferred. Examples of alcohol-soluble nylon resins include homopolymer or copolymer nylons such as 6-nylon, 66-nylon, 610-nylon, 11-nylon, and 12-nylon, and resins obtained by chemically modifying nylons such as N-alkoxymethyl-modified nylons.

[0036] Examples of solvents for dissolving or dispersing resin materials include water, alcohols such as methanol, ethanol, and butanol, glymes such as methyl carbitol and butyl carbitol, chlorine-based solvents such as dichloroethane, chloroform, and trichloroethane, acetone, dioxolane, mixed solvents of two or more of these solvents, etc. Among these solvents, non-halogenated organic solvents are preferably used in consideration of the global environment.

[0037] The coating solution for the undercoat layer may contain inorganic compound fine particles. The inorganic compound fine particles of the undercoat layer have a different purpose from the inorganic compound fine particles of the outermost layer, and may be the same compound or different compounds. The inorganic compound fine particles can easily adjust the volume resistivity of the undercoat layer, can further suppress the injection of charges into the laminated type photosensitive layer, and can maintain the electrical characteristics of the photoreceptor under various environments. Examples of inorganic compound fine particles include titanium oxide, aluminum oxide, aluminum hydroxide, and tin oxide. The ratio (C / D) of the total weight C of the binder resin and the inorganic compound particles to the weight D of the solvent in the coating liquid for the undercoat layer is preferably from 1 / 99 to 40 / 60, particularly preferably from 2 / 98 to 30 / 70. The ratio E / F of the weight E of the binder resin to the weight F of the inorganic compound particles is preferably 90 / 10 to 1 / 99, and particularly preferably 70 / 30 to 5 / 95.

[0038] In order to disperse the inorganic compound particles in the coating liquid for the undercoat layer, known devices such as a ball mill, a sand mill, an attritor, a vibration mill, an ultrasonic disperser, and a paint shaker may be used. The method for applying the coating solution for the undercoat layer may be appropriately selected from among the most suitable methods taking into consideration the physical properties of the coating solution and productivity. Examples of the method include spraying, bar coating, roll coating, blade coating, ring coating, and dip coating. Among these, the dip coating method is a method in which a substrate is immersed in a coating tank filled with a coating liquid, and then pulled up at a constant speed or a gradually changing speed to form a layer on the surface of the substrate, and is relatively simple and has excellent productivity and cost, so that it can be suitably used for manufacturing photoreceptors. The apparatus used for the dip coating method may be provided with a coating liquid dispersion device, typically an ultrasonic generator, in order to stabilize the dispersibility of the coating liquid.

[0039] The solvent in the coating film may be removed by natural drying, but the solvent in the coating film may also be removed forcibly by heating. The temperature in such a drying step is not particularly limited as long as it is a temperature at which the solvent used can be removed, but a temperature of about 50 to 140°C is appropriate, and a temperature of about 80 to 130°C is particularly preferable. If the drying temperature is less than 50°C, the drying time may be long and the solvent may not evaporate sufficiently and remain in the photoreceptor layer, while if the drying temperature exceeds about 140°C, the electrical characteristics of the photoreceptor may deteriorate during repeated use, resulting in poor quality of the obtained image. Such temperature conditions are common not only to the formation of the undercoat layer but also to the formation of layers such as a laminated type photosensitive layer, which will be described later, and other treatments.

[0040] The thickness of the undercoat layer is not particularly limited, but is preferably 0.01 to 20 μm, and more preferably 0.05 to 10 μm. If the thickness of the undercoat layer is less than 0.01 μm, it will not function as an undercoat layer, and it will not be possible to cover defects in the conductive support to obtain a uniform surface, and it may not be possible to prevent injection of charges from the conductive support into the laminated photosensitive layer. On the other hand, if the thickness of the undercoat layer is more than 20 μm, it will be difficult to form a uniform undercoat layer, and the sensitivity of the photoreceptor may also decrease. When the conductive support is made of aluminum, a layer containing alumite (alumite layer) may be formed as the undercoat layer.

[0041] <Charge generating layer 13> The charge generating layer has a function of generating charges by absorbing light irradiated by, for example, semiconductor laser light in an image forming apparatus, and contains a charge generating substance as a main component and, if necessary, a binder resin and additives.

[0042] The charge generating material can be a compound used in the field, specifically, azo pigments such as monoazo pigments, bisazo pigments and trisazo pigments; indigo pigments such as indigo and thioindigo; perylene pigments such as peryleneimide and perylene acid anhydride; polycyclic quinone pigments such as anthraquinone and pyrenequinone; phthalocyanine pigments such as metal phthalocyanine and metal-free phthalocyanine such as titanyl phthalocyanine; organic photoconductive materials such as squarylium dyes, pyrylium salts, thiopyrylium salts, triphenylmethane dyes; and inorganic photoconductive materials such as selenium and amorphous silicon, and can be appropriately selected and used from those having sensitivity in the exposure wavelength range. These charge generating materials can be used alone or in combination of two or more. Among these charge generating materials, those represented by the following general formula (A):

[0043] [ka]

[0044] (In the formula, X 1 , X 2 , X 3 and X 4 are the same or different and each is a halogen atom, an alkyl group, or an alkoxy group, and r, s, y, and z are the same or different and each is an integer of 0 to 4. It is preferable to use titanyl phthalocyanine represented by the following formula: Titanyl phthalocyanine is a charge-generating material that has high charge generation efficiency and charge injection efficiency in the emission wavelength range (near-infrared light) of currently commonly used laser light and LED light. It generates a large amount of charge by absorbing light and can efficiently inject the generated charge into the charge-transport material without accumulating it inside.

[0045] The titanyl phthalocyanine represented by the general formula (A) can be produced by known production methods such as the method described in Phthalocyanine Compounds by Moser, Frank H. and Arthur L. Thomas, Reinhold Publishing Corp., New York, 1963. For example, among the titanyl phthalocyanine compounds represented by the general formula (A), in the case of an unsubstituted titanyl phthalocyanine in which r, s, y, and z are 0, it can be obtained by synthesizing dichlorotitanyl phthalocyanine by heating and melting phthalonitrile and titanium tetrachloride or by heating and reacting them in a suitable solvent such as α-chloronaphthalene, and then hydrolyzing the resultant with a base or water. Alternatively, the titanyl phthalocyanine composition can be produced by reacting isoindoline with a titanium tetraalkoxide such as tetrabutoxytitanium under heating in a suitable solvent such as N-methylpyrrolidone.

[0046] The method for forming the charge generation layer includes a method of vacuum-depositing the charge generation material on the conductive support, and a method of dispersing the charge generation material in a solvent and applying a coating liquid for the charge generation layer onto the conductive support. Among these, a method of dispersing the charge generation material in a binder resin solution obtained by mixing a binder resin in a solvent by a conventionally known method and applying the coating liquid for the charge generation layer onto the conductive support is preferred. This method will be described below.

[0047] The binder resin is not particularly limited, and any resin known in the art can be used. Examples of the binder resin include polyester, polystyrene, polyurethane, phenolic resin, alkyd resin, melamine resin, epoxy resin, silicone resin, acrylic resin, methacrylic resin, polycarbonate, polyarylate, polyphenoxy, polyvinyl butyral, and polyvinyl formal resins, as well as copolymer resins containing two or more of the repeating units constituting these resins. Examples of the copolymer resin include insulating resins such as vinyl chloride-vinyl acetate copolymer resin, vinyl chloride-vinyl acetate-maleic anhydride copolymer resin, and acrylonitrile-styrene copolymer resin. These resins can be used alone or in combination of two or more.

[0048] Examples of the solvent include halogenated hydrocarbons such as dichloromethane and dichloroethane, ketones such as acetone, methyl ethyl ketone and cyclohexanone, esters such as ethyl acetate and butyl acetate, ethers such as tetrahydrofuran (THF) and dioxane, alkyl ethers of ethylene glycol such as 1,2-dimethoxyethane, aromatic hydrocarbons such as benzene, toluene and xylene, and aprotic polar solvents such as N,N-dimethylformamide and N,N-dimethylacetamide. These solvents can be used alone or in combination of two or more.

[0049] The compounding ratio between the charge generating substance and the binder resin is preferably such that the proportion of the charge generating substance is within a range of 10 to 99 mass %. If the ratio of the charge generating material is less than 10% by mass, the sensitivity may decrease. On the other hand, if the ratio of the charge generating material is more than 99% by mass, not only the film strength of the charge generating layer decreases, but also the dispersibility of the charge generating material decreases, the number of coarse particles increases, and the surface charge decreases in areas other than those that should be erased by exposure, resulting in image defects, particularly image fogging called black spots, in which toner adheres to a white background and tiny black spots are formed.

[0050] Before dispersing the charge generating material in the binder resin solution, the charge generating material may be pulverized in advance using a pulverizer such as a ball mill, a sand mill, an attritor, a vibration mill, or an ultrasonic disperser. Examples of dispersing machines used when dispersing the charge generating material in the binder resin solution include a paint shaker, a ball mill, a sand mill, etc. Appropriate dispersion conditions may be selected so as to prevent the incorporation of impurities due to wear of the container and members constituting the dispersing machine. The coating liquid for the charge generating layer may be applied by the same method as the coating liquid for the undercoat layer, and a dip coating method is particularly preferred.

[0051] The thickness of the charge generating layer is not particularly limited, but is preferably 0.05 to 5 μm, and more preferably 0.1 to 1 μm. If the thickness of the charge generating layer is less than 0.05 μm, the efficiency of light absorption decreases, and the sensitivity of the photoconductor may decrease. On the other hand, if the thickness of the charge generating layer exceeds 5 μm, the charge transfer inside the charge generating layer becomes the rate-limiting step in the process of erasing the charge on the surface of the laminated photosensitive layer, and the sensitivity of the photoconductor may decrease.

[0052] <Charge transport layer 14> The charge transport layer has the function of receiving the charges generated by the charge generating substance and transporting them to the surface of the photoreceptor, and contains a charge transport substance, a binder resin, silica particles, and, if necessary, additives.

[0053] As the charge transport material, compounds used in the art can be used. Specific examples thereof include carbazole derivatives, pyrene derivatives, oxazole derivatives, oxadiazole derivatives, thiazole derivatives, thiadiazole derivatives, triazole derivatives, imidazole derivatives, imidazolone derivatives, imidazolidine derivatives, bisimidazolidine derivatives, styryl compounds, hydrazone compounds, polycyclic aromatic compounds, indole derivatives, pyrazoline derivatives, oxazolone derivatives, benzimidazole derivatives, quinazoline derivatives, benzofuran derivatives, acridine derivatives, phenazine derivatives, aminostilbene derivatives, triarylamine derivatives, triarylmethane derivatives, phenylenediamine derivatives, stilbene derivatives, butadiene derivatives, enamine derivatives, benzidine derivatives, polymers having groups derived from these compounds in the main chain or side chain (poly-N-vinylcarbazole, poly-1-vinylpyrene, ethylcarbazole-formaldehyde resin, triphenylmethane polymer, poly-9-vinylanthracene, etc.), and polysilanes. These charge transport materials can be used alone or in combination of two or more.

[0054] Among these various charge transport materials, in terms of electrical properties, durability and chemical stability, stilbene derivatives, butadiene derivatives, enamine derivatives and compounds in which a plurality of these compounds are combined are preferred, and stilbene derivatives are more preferred, and are represented by the following general formula (I):

[0055] [ka]

[0056] (In the formula, R1, R2, R5, and R6 are the same or different and each is an alkyl group, an alkoxy group, an aryl group, or an aralkyl group; m, n, p, and q are the same or different and each is an integer of 0 to 3; and R3 and R4 are the same or different and each is a hydrogen atom or an alkyl group.) The stilbene compounds represented by the following formula are particularly preferred in that they cause little increase in residual potential and little deterioration in sensitivity and can exhibit good electrophotographic properties.

[0057] The substituents R1, R2, R5 and R6 in the general formula (I) will be described below. Examples of the alkyl group include alkyl groups having 1 to 6 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, and n-hexyl. Examples of the alkoxy group include alkoxy groups having 1 to 6 carbon atoms, such as methoxy, ethoxy, n-propoxy, isopropoxy, tert-butoxy, n-pentyloxy, and n-hexyloxy. Examples of the aryl group include phenyl, naphthyl, anthryl, phenanthryl, fluorenyl, biphenylyl, and o-terphenyl. Aralkyl groups include, for example, benzyl, phenethyl, benzhydryl, trityl, and the like. Examples of the halogen atom include fluorine, chlorine, bromine, and iodine.

[0058] The indices m, n, p and q of the substituents R1, R2, R5 and R6 are the same or different and are integers of 0 to 3, and when the indices are 2 or more, the respective substituents may be different from each other. In addition, examples of the alkyl group of the substituents R3 and R4 in the general formula (I) include alkyl groups having 1 to 3 carbon atoms, such as methyl, ethyl, n-propyl, and isopropyl. The stilbene compound represented by the general formula (I) can be synthesized, for example, by the method described in Japanese Patent No. 3272257.

[0059] Examples of the stilbene compound represented by the general formula (I) include the following compounds (1) to (3), and compound (1) is particularly preferred in terms of printing durability when used in a laminated photosensitive layer.

[0060] [ka]

[0061] The charge transport material preferably has an ionization potential of 5.4 eV or more and 5.55 eV or less. When the ionization potential is less than 5.4 eV, Oxidizing gases etc., may become large, resulting in poor stability of the initial electrical characteristics. On the other hand, the incorporation of worn metal oxide into the photosensitive layer may form trap sites for hole transport, and if the ionization potential exceeds 5.55 eV, the effect of trapping holes may become large, leading to an increase in the residual potential and deterioration of sensitivity. Therefore, if the purpose is long-term use, an ionization potential in the above range is appropriate. The ionization potential of the charge transport material is particularly preferably 5.4 eV or more and 5.52 eV or less.

[0062] A preferred method for forming the charge transport layer is to disperse the charge transport material and inorganic compound particles in a binder resin solution obtained by mixing a binder resin in a solvent by a conventionally known method, and then coat the coating liquid for the charge transport layer on the charge generating layer. This method will be described below.

[0063] The binder resin is not particularly limited, and any resin known in the art can be used, for example, vinyl polymer resins such as polymethyl methacrylate, polystyrene, polyvinyl chloride, and copolymer resins thereof, as well as resins such as polycarbonate, polyester, polyester carbonate, polysulfone, polyphenoxy, epoxy resin, silicone resin, polyarylate, polyphenylene oxide, polyamide, polyether, polyurethane, polyacrylamide, and phenol resin, and thermosetting resins obtained by partially crosslinking these resins, etc. These binder resins can be used alone or in combination of two or more.

[0064] Among these, polystyrene, polycarbonate, polyarylate and polyphenylene oxide have a volume resistivity of 1013 Ω or more, has excellent electrical insulation properties, and is also excellent in film-forming properties and potential characteristics, and is preferably represented by the following structural formula (B): [ka] or the polycarbonate Z skeleton represented by the following structural formula (C):

[0065] [ka] Particularly preferred is a resin having a polyarylate skeleton represented by the following formula: and further preferred is a resin having a polyarylate skeleton represented by the following formula: The use of these resins reduces damage to the photoreceptor due to electrical fatigue, improves its resistance, and enables stable image characteristics to be provided throughout its life, thereby realizing high printing durability and a long life for the photoreceptor.

[0066] The ratio A / B of the charge transport material (A) to the binder resin (B) is preferably from 10 / 12 to 10 / 30. If the ratio A / B is less than 10 / 30 and the ratio of the binder resin is high, when the charge transport layer is formed by dip coating, the viscosity of the coating liquid increases, leading to a decrease in the coating speed and a significant decrease in productivity. In addition, if the amount of solvent in the coating liquid is increased to suppress the increase in the viscosity of the coating liquid, a blushing phenomenon may occur and the formed charge transport layer may become cloudy. On the other hand, if the ratio A / B exceeds 10 / 12 and the ratio of the binder resin is low, the printing durability will be lower than when the ratio of the binder resin is high, and the amount of wear of the laminated photosensitive layer may increase.

[0067] The content of the silica particles is preferably 7% by mass or more and 25% by mass or less in the charge transport layer that is the outermost layer, as described in the section <Content of Silica Particles>.

[0068] The charge transport layer may contain additives such as a plasticizer or a leveling agent, if necessary, in order to improve film formability, flexibility and surface smoothness. Examples of the plasticizer include dibasic acid esters such as phthalic acid esters, fatty acid esters, phosphate esters, chlorinated paraffin, and epoxy type plasticizers. The leveling agent may be, for example, a silicone-based leveling agent. The charge transport layer may contain fine particles of an inorganic or organic compound in order to increase the mechanical strength and improve the electrical characteristics.

[0069] Examples of the solvent include aromatic hydrocarbons such as benzene, toluene, xylene, and monochlorobenzene, halogenated hydrocarbons such as dichloromethane and dichloroethane, ethers such as THF, dioxane, and dimethoxymethyl ether, and aprotic polar solvents such as N,N-dimethylformamide. If necessary, solvents such as alcohols, acetonitrile, or methyl ethyl ketone can also be added. Among these solvents, non-halogenated organic solvents are preferably used in consideration of the global environment. These solvents can be used alone or in combination of two or more.

[0070] The charge transport layer is formed, for example, in the same manner as in the case of forming the above-mentioned charge generation layer 13, by preparing a coating liquid for the charge transport layer by dissolving or dispersing the charge transport material and binder resin, and, if necessary, the above-mentioned additives, in an appropriate solvent, and applying this coating liquid onto the charge generation layer 13 by a spray method, a bar coating method, a roll coating method, a blade method, a ring method, a dip coating method, or the like. Among these coating methods, the dip coating method is particularly excellent in various respects as described above, and is therefore often used in forming the charge transport layer.

[0071] The charge transport layer of the photoreceptor of the present invention contains specific amounts of Na and / or K, and further specific amounts of Ca and / or Mg, in specific ratios relative to the silica particles. In order to incorporate these elements into the charge transport layer, for example, when the charge transport layer is formed by a coating method, a compound containing these elements, specifically an oxide, may be added to a coating liquid for the charge transport layer. As an example of the method of addition, a coating solution is prepared using equipment made of a material containing a compound containing these elements, and the compound containing these elements is mixed into the coating solution by abrasion of the equipment. The amount of the compound to be mixed may be adjusted by the preparation method of the coating solution and the treatment time. In addition, a specific amount of a compound containing the above element may be added to a coating solution prepared under conditions free from contamination by the material of the device. The contents and ratios of the silica particles and each element are considered to be approximately equivalent in terms of the solid content in the coating liquid and the measured values ​​in the formed charge transport layer.

[0072] The thickness of the charge transport layer is not particularly limited, but is preferably 5 to 50 μm, and more preferably 10 to 40 μm. If the thickness of the charge transport layer is less than 5 μm, the charge retention ability of the photoreceptor surface may decrease, whereas if the thickness of the charge transport layer is more than 50 μm, the resolution of the photoreceptor may decrease.

[0073] <Second charge transport layer 16> 2, the charge transport layer of the photoreceptor of the present invention may be a first charge transport layer 15 and a second charge transport layer 16 sequentially laminated on a charge generating layer, with the first charge transport layer 15 containing a charge transport material and a binder resin, and the second charge transport layer 16 containing a charge transport material, a binder resin, and silica particles 18. That is, the charge transport layer may be composed of two layers, with the silica particles 18 being contained in the second charge transport layer 16, which is the outermost layer of the photoreceptor. This allows for functional separation in each layer, and by containing silica only in the second charge transport layer and making the outermost layer a hardened film, the printing durability of the entire photosensitive layer can be improved.

[0074] The charge transport material, binder resin and silica particles may be those described in the previous section <Charge Transport Layer>. The first charge transport layer 15 and the second charge transport layer 16 are formed, for example, in the same manner as in the case of forming the charge generation layer 13 and the charge transport layer 14 described above, by dissolving or dispersing the components in an appropriate solvent to prepare a coating liquid for the first charge transport layer and a coating liquid for the second charge transport layer, respectively, and applying the coating liquid onto the charge generation layer 13 and the first charge transport layer 15, respectively, by a spray method, a bar coating method, a roll coating method, a blade method, a ring method, a dip coating method, or the like. Among these coating methods, the dip coating method in particular is excellent in various respects as described above, and is therefore often used when forming these layers.

[0075] The thickness of the first charge transport layer is not particularly limited, but is preferably 15 to 50 μm, and more preferably 25 to 40 μm. The thickness of the second charge transport layer is not particularly limited, but is preferably 5 to 20 μm, and more preferably 5 to 10 μm. Photoconductors that are used repeatedly over a long period of time are designed to be mechanically durable and resistant to wear. However, in actual equipment, ozone and NOx gases are generated from the charging members and adhere to the surface of the photoconductor, causing image deletion. To prevent this image deletion, the laminated photosensitive layer must be worn at a certain rate or higher, and in consideration of long-term repeated use, the second charge transport layer is preferably at least 1.0 μm thick. Furthermore, if the thickness of the second charge transport layer exceeds 8.0 μm, problems such as an increase in residual potential and a decrease in fine dot reproducibility may occur.

[0076] (2) Image forming apparatus 100 The image forming apparatus of the present invention is characterized by comprising at least the photoconductor of the present invention, charging means for charging the photoconductor, exposure means for exposing the charged photoconductor to form an electrostatic latent image, developing means for developing the electrostatic latent image formed by exposure to form a toner image (visible image), transfer means for transferring the toner image formed by development onto a recording medium, fixing means for fixing the transferred toner image on the recording medium to form an image, cleaning means for removing and recovering toner remaining on the photoconductor, and discharging means for discharging surface charge remaining on the photoconductor. The image forming apparatus of the present invention and its operation will be described with reference to the drawings, but the present invention is not limited to the following description.

[0077] FIG. 3 is a schematic side view showing the configuration of the image forming apparatus of the present invention. The image forming apparatus (laser printer) 100 in Fig. 3 includes the photoreceptor 1 of the present invention, an exposure means (semiconductor laser) 31, a charging means (charger) 32, a developing means (developer) 33, a transfer means (transfer charger) 34, a conveyor belt (not shown), a fixing means (fixer) 35, and a cleaning means (cleaner) 36. Reference numeral 51 denotes a recording medium (recording paper or transfer paper). The photoreceptor 1 may be the photoreceptor 2 of the present invention.

[0078] Photoconductor 1 is rotatably supported by the main body of image forming apparatus 100, and is driven to rotate around rotation axis 44 in the direction of arrow 41 by driving means (not shown). The driving means includes, for example, an electric motor and a reduction gear, and transmits its driving force to a conductive support constituting the core body of photoconductor 1, thereby driving and rotating photoconductor 1 at a predetermined peripheral speed. Charging means (charger) 32, exposure means 31, developing means (developer) 33, transfer means (transfer charger) 34, and cleaning means (cleaner) 36 are provided in this order along the outer circumferential surface of photoconductor 1 from the upstream side to the downstream side in the rotation direction of photoconductor 1 indicated by arrow 41.

[0079] The charger 32 is a charging means for uniformly charging the outer circumferential surface of the photoreceptor 1 to a predetermined potential. The exposure means 31 has a semiconductor laser as a light source, and irradiates the surface of the photoreceptor 1 between the charger 32 and the developer 33 with a laser beam light output from the light source, thereby exposing the charged outer peripheral surface of the photoreceptor 1 according to image information. The light is repeatedly scanned in the direction of extension of the rotation axis 44 of the photoreceptor 1, which is the main scanning direction, and these are focused to sequentially form electrostatic latent images on the surface of the photoreceptor 1. In other words, the charge amount of the photoreceptor 1, which has been uniformly charged by the charger 32, differs depending on whether it is irradiated with the laser beam or not, and an electrostatic latent image is formed.

[0080] The developing device 33 is a developing means that develops the electrostatic latent image formed on the surface of the photoconductor 1 by exposure with a developer (toner), and is provided facing the photoconductor 1. The developing device 33 includes a developing roller 33a that supplies toner to the outer peripheral surface of the photoconductor 1, and a casing 33b that rotatably supports the developing roller 33a about a rotation axis parallel to the rotation axis 44 of the photoconductor 1 and contains a developer including toner in its internal space.

[0081] The transfer charger 34 is a transfer means that transfers a toner image, which is a visible image formed on the outer peripheral surface of the photoconductor 1 by development, onto a transfer paper 51, which is a recording medium, supplied between the photoconductor 1 and the transfer charger 34 from the direction of the arrow 42 by a transport means (not shown). The transfer charger 34 is, for example, a contact type transfer means that includes a charging means and transfers the toner image onto the transfer paper 51 by applying a charge of the opposite polarity to that of the toner to the transfer paper 51.

[0082] The cleaner 36 is a cleaning means for removing and recovering the toner remaining on the outer peripheral surface of the photoreceptor 1 after the transfer operation by the transfer charger 34, and includes a cleaning blade 36a for removing the toner remaining on the outer peripheral surface of the photoreceptor 1, and a recovery casing 36b for containing the toner removed by the cleaning blade 36a. The cleaner 36 is also provided together with a static elimination lamp (not shown).

[0083] Furthermore, in the image forming apparatus 100, a fixing device 35, which is a fixing means for fixing a transferred image, is provided downstream of the conveyance of the transfer paper 51 that has passed between the photoconductor 1 and the transfer charger 34. The fixing device 35 includes a heating roller 35a having a heating means (not shown), and a pressure roller 35b that is provided opposite the heating roller 35a and is pressed against the heating roller 35a to form a contact portion. Reference numeral 37 denotes a separating means for separating the transfer paper from the photosensitive member, and reference numeral 38 denotes a casing for accommodating the above-mentioned means of the image forming apparatus.

[0084] The image forming operation by this image forming apparatus 100 is carried out as follows. First, when the photoconductor 1 is rotated in the direction of arrow 41 by the driving means, the surface of the photoconductor 1 is uniformly charged to a predetermined positive potential by the charger 32, which is provided upstream of the image-forming point of the light by the exposure means 31 in the rotational direction of the photoconductor 1.

[0085] Next, light according to image information is irradiated from exposure means 31 onto the surface of photoreceptor 1. This exposure removes surface charge from the areas of photoreceptor 1 irradiated with light, creating a difference in surface potential between the areas irradiated with light and the areas not irradiated with light, forming an electrostatic latent image. Toner is supplied from a developing device 33, which is provided downstream in the rotational direction of the photoconductor 1 from the imaging point of the light by the exposure means 31, to the surface of the photoconductor 1 on which the electrostatic latent image is formed, thereby developing the electrostatic latent image and forming a toner image.

[0086] In synchronization with the exposure of the photoconductor 1, a transfer paper 51 is supplied between the photoconductor 1 and the transfer charger 34. The transfer charger 34 gives the supplied transfer paper 51 a charge of the opposite polarity to that of the toner, and the toner image formed on the surface of the photoconductor 1 is transferred onto the transfer paper 51. The transfer paper 51 onto which the toner image has been transferred is transported by the transport means to the fixing device 35, and is heated and pressurized as it passes through the contact area between the heating roller 35a and the pressure roller 35b of the fixing device 35, and the toner image is fixed onto the transfer paper 51 to form a robust image. The transfer paper 51 on which the image has been formed in this way is discharged to the outside of the image forming apparatus 100 by the transport means.

[0087] Meanwhile, the toner remaining on the surface of the photoreceptor 1 after the transfer of the toner image by the transfer charger 34 is peeled off from the surface of the photoreceptor 1 and collected by the cleaner 36. The charge on the surface of the photoreceptor 1 from which the toner has been removed in this manner is removed by light from a discharging lamp, and the electrostatic latent image on the surface of the photoreceptor 1 disappears. The photoreceptor 1 is then rotated again, and the series of operations starting with charging are repeated again to form images continuously.

[0088] (3) Manufacturing method of electrophotographic photoreceptor The method for producing an electrophotographic photoreceptor of the present invention is characterized by including a step of forming a charge transport layer using a coating liquid for a charge transport layer that contains at least a charge transport material, a binder resin, and silica particles, and also contains 0.1 ppm or more and 20 ppm or less of Na element and / or K element based on the solid content. The materials constituting each layer including the charge transport layer, the preparation conditions and the like are as described in (1) Electrophotographic Photoreceptor.

[0089] (4) Coating solution for charge transport layer The coating liquid for a charge transport layer of the present invention is characterized by containing at least a charge transport material, a binder resin and silica particles, and also containing 0.1 ppm to 20 ppm of Na element and / or K element based on the solid content. The constituent materials of the coating solution for the charge transport layer, the amounts of the materials blended, etc. are as described in (1) <Charge Transport Layer> of the Electrophotographic Photoreceptor. EXAMPLES

[0090] The present invention will be specifically described below with reference to examples and comparative examples based on the drawings, but the present invention is not limited to these examples. The ionization potential of the charge transport material used in the examples and comparative examples, the elemental analysis of the charge transport layer of the prepared photoreceptor, and the surface roughness of the outermost layer were measured as follows.

[0091] [Ionization potential of charge transport materials] The ionization potential (eV) is measured using an air photoelectron spectrometer (manufactured by Riken Keiki Co., Ltd., model: AC-2) at an output of 10 to 100 nW.

[0092] [Elemental analysis of the charge transport layer] The Na, K, Ca and Mg elements in the charge transport layer are analyzed using an ICP emission spectrometer (manufactured by Thermo Fisher Scientific, model: iCAP-6500).

[0093] [Surface roughness of the outermost layer Rz] Using a surface roughness measuring device (Tokyo Seimitsu Co., Ltd., model: Surfcom1400D), measure the surface roughness Rz (μm) of the center part with the horizontal direction of the outermost surface layer of the photoconductor as the measurement position, using a method with a reference length of 0.8 mm, a cutoff wavelength of 0.8 mm, a measurement speed of 0.1 mm / sec, and a Gaussian cutoff type. This Rz corresponds to the ten-point surface roughness Rz defined in JIS-B-0601 (1994).

[0094] Example 1 Three parts by weight of titanium oxide (manufactured by Ishihara Sangyo Kaisha, Ltd., product name: Tiebaque TTO-D-1) and two parts by weight of copolymer polyamide (nylon) (manufactured by Toray Industries, Inc., product name: Amilan (registered trademark), grade: CM8000) were added to 25 parts by weight of methyl alcohol, and the mixture was dispersed for eight hours using a paint shaker to prepare 3 liters of coating solution for the undercoat layer. The obtained undercoat layer coating liquid was filled into a coating tank, and an aluminum drum-shaped support having a diameter of 30 mm and a length of 255 mm as the conductive support 11 was immersed in it and then removed. The obtained coating film was allowed to dry naturally, thereby forming an undercoat layer 12 with a thickness of 1 μm on the conductive support 11.

[0095] Titanyl phthalocyanine represented by the following structural formula, which was to be used as a charge generating material, was prepared in advance. [ka]

[0096] 29.2 g of diiminoisoindoline and 200 ml of sulfolane were mixed, and 17.0 g of titanium tetraisopropoxide was added and reacted under a nitrogen atmosphere at 140° C. for 2 hours. The resulting reaction mixture was allowed to cool, and the precipitate was collected by filtration, washed successively with chloroform and a 2% aqueous hydrochloric acid solution, further washed successively with water and methanol, and dried to obtain 25.5 g of blue-purple crystals. As a result of chemical analysis of the obtained compound, it was confirmed that it was titanyl phthalocyanine represented by the above structural formula (yield 88.5%).

[0097] 1 part by weight of the obtained titanyl phthalocyanine and 1 part by weight of butyral resin (manufactured by Sekisui Chemical Co., Ltd., product name: S-LEC BM-2) were added to 98 parts by weight of methyl ethyl ketone, and the mixture was dispersed for 2 hours using a paint shaker to prepare 3 liters of a coating solution for the charge generating layer. The obtained coating liquid for the charge generating layer was applied onto the undercoat layer 12 by the same immersion method as in the case of forming the undercoat layer, and the obtained coating film was allowed to dry naturally to form a charge generating layer 13 with a thickness of 0.3 μm.

[0098] Next, in a 140 mL soda-lime glass container, 4 g of silica particles (number average primary particle size 16 nm, surface treated with dimethyldichlorosilane, manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) R972) were suspended in 36 g of tetrahydrofuran, and the suspension was stirred for 15 hours using a stirrer (manufactured by Shibata Scientific Co., Ltd., model: M-103) and a stirring blade. To the obtained silica particle (silica filler) suspension, 13.8 g of compound (1) represented by the following structural formula as a charge transport material, 22.2 g of polycarbonate (manufactured by Teijin Chemical Co., Ltd., product name: TS2040), and 105.8 g of tetrahydrofuran were added, mixed, and stirred for 30 hours using a stirrer and stirring blade. The resulting mixture was subjected to 6-pass dispersion treatment using a particle dispersion device (Microfluidics, model: Microfluidizer M110P) to prepare 133 g of a coating solution for the charge transport layer, which was then allowed to stand at 20°C.

[0099] [ka]

[0100] The obtained coating liquid for the charge transport layer was applied onto the charge generation layer 13 by the same immersion method as in the case of forming the undercoat layer, and the obtained coating film was dried at 115°C for 1.5 hours to form a charge transport layer 14 with a thickness of 35 μm, thereby obtaining the photoreceptor 1 shown in Figure 1. Compound (1) (stilbene compound) previously prepared according to the method described in Japanese Patent No. 3272257 was used as a charge transport material (ionization potential 5.47 eV). Figure 4 is a scanning transmission electron microscope (SEM) image showing the dispersion state of silica particles on the surface of the charge transport layer of the obtained photoreceptor. From this figure, it can be seen that the interactions between the silica particles are optimally expressed, forming a loose aggregate structure like a uniform network structure in which the silica particles are interconnected, that is, a sea-island structure of islands of silica particles in the black part against a sea of ​​binder resin in the white part.

[0101] Example 2 A photoreceptor 1 shown in FIG. 1 was obtained in the same manner as in Example 1, except that the coating liquid for the charge transport layer was prepared as follows. Into a 250 mL polypropylene container were added 9 g of silica particles (number average primary particle size 16 nm, surface treated with dimethyldichlorosilane, manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) R972) and 81 g of tetrahydrofuran, and soda-lime glass beads (150 g) having a diameter of 2 mm were added and mixed. The resulting mixture was further treated for 10 hours in a ball mill (manufactured by Eishin Co., Ltd., model: benchtop ball mill BM-15). The glass beads were removed from the resulting mixture, and 13.0 g of compound (1) as a charge transport material, 20.8 g of polycarbonate (manufactured by Teijin Chemical Co., Ltd., product name: TS2040) and 70.9 g of tetrahydrofuran were added and mixed, followed by stirring for 30 hours using a stirrer and stirring blade. The resulting mixture was subjected to 6-pass dispersion treatment using a particle dispersion device to prepare 148 g of a coating liquid for the charge transport layer, and was allowed to stand at 20°C.

[0102] Example 3 In preparing the silica filler suspension of the charge transport layer coating liquid, the silica particles were changed from 9 g to 4 g, and tetrahydrofuran from 81 g to 36 g, and the charge transport material added to the obtained silica filler suspension was changed from 13.0 g to 13.8 g of compound (1), from 20.8 g to 22.2 g of polycarbonate, and from 70.9 g to 105.8 g of tetrahydrofuran. The photoreceptor 1 shown in FIG. 1 was obtained in the same manner as in Example 2.

[0103] Example 4 A photoreceptor 1 shown in FIG. 1 was obtained in the same manner as in Example 1, except that in the preparation of the silica filler suspension in the coating liquid for the charge transport layer, the stirring time was changed from 15 hours to 8 hours.

[0104] Example 5 In preparing the silica filler suspension for the charge transport layer coating liquid, the photoreceptor 1 shown in FIG. 1 was obtained in the same manner as in Example 1, except that the silica particles were changed to silica particles (number average primary particle size 40 nm, hexamethyldisilazane surface treatment, manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) RX50).

[0105] Example 6 In preparing the silica filler suspension of the charge transport layer coating liquid, the silica particles were changed from 4 g to 3 g, and tetrahydrofuran was changed from 36 g to 27 g, and the charge transport material added to the obtained silica filler suspension was changed from 13.8 g to 16.6 g of compound (1), from 22.2 g to 26.6 g of polycarbonate, and from 105.8 g to 136.6 g of tetrahydrofuran. The photoreceptor 1 shown in FIG. 1 was obtained in the same manner as in Example 1.

[0106] Example 7 In preparing the silica filler suspension of the charge transport layer coating liquid, the silica particles were changed from 4 g to 10 g, the tetrahydrofuran from 36 g to 90 g, and the stirring time from 15 to 45 hours, and the charge transport material added to the obtained silica filler suspension was changed from 13.8 g to 11.5 g of compound (1), from 22.2 g to 18.5 g of polycarbonate, and from 105.8 g to 51.8 g of tetrahydrofuran. The photoreceptor 1 shown in FIG. 1 was obtained in the same manner as in Example 1.

[0107] Example 8 In preparing the silica filler suspension of the charge transport layer coating liquid, the silica particles were changed from 9 g to 3 g, and tetrahydrofuran was changed from 81 g to 27 g, and the charge transport material added to the obtained silica filler suspension was changed from 13.0 g to 15.3 g of compound (1), from 20.8 g to 24.5 g of polycarbonate, and from 70.9 g to 124.9 g of tetrahydrofuran. The photoreceptor 1 shown in FIG. 1 was obtained in the same manner as in Example 2.

[0108] Example 9 In preparing the silica filler suspension of the charge transport layer coating liquid, the silica particles were changed from 4 g to 9 g of silica particles (number average primary particle size 16 nm, surface treatment with hexamethyldisilazane, manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) NX130), and tetrahydrofuran was changed from 36 g to 81 g. The charge transport material added to the obtained silica filler suspension was changed from 13.8 g to 12.3 g of compound (1), from 22.2 g to 19.6 g of polycarbonate, and from 105.8 g to 64.0 g of tetrahydrofuran. The photoreceptor 1 shown in FIG. 1 was obtained in the same manner as in Example 2.

[0109] Example 10 In preparing the silica filler suspension of the charge transport layer coating liquid, the silica particles were changed from 4 g to 9 g of silica particles (number average primary particle size 16 nm, surface treatment with hexamethyldisilazane, manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) NX130), and tetrahydrofuran was changed from 36 g to 81 g. The charge transport material added to the obtained silica filler suspension was changed from 13.8 g to 10.4 g of compound (1), from 22.2 g to 16.6 g of polycarbonate, and from 105.8 g to 46.6 g of tetrahydrofuran. The photoreceptor 1 shown in FIG. 1 was obtained in the same manner as in Example 2.

[0110] Example 11 In preparing the silica filler suspension of the charge transport layer coating liquid, the amount of silica particles was changed from 4 g to 3 g, and tetrahydrofuran was changed from 36 g to 27 g, and the amount of compound (1) added to the obtained silica filler suspension as the charge transport material was changed from 13.8 g to 16.6 g, polyarylate (manufactured by Mitsubishi Chemical Corporation, product name: E2-400) was changed from 22.2 g to 26.6 g, and tetrahydrofuran was changed from 105.8 g to 136.6 g. The photoreceptor 1 shown in FIG. 1 was obtained in the same manner as in Example 1.

[0111] Example 12 In preparing a coating solution for a charge transport layer, a charge transport material having the following structural formula (a): [ka] A photoreceptor 1 shown in FIG. 1 was obtained in the same manner as in Example 1, except that a triphenylamine compound (TPD) represented by the following formula (ionization potential: 5.51 eV, product name: D2448, manufactured by Tokyo Chemical Industry Co., Ltd.) was used.

[0112] Example 13 In preparing a coating solution for a charge transport layer, a compound having the following structural formula (b): [ka] A photoreceptor 1 shown in FIG. 1 was obtained in the same manner as in Example 1, except that a styryl compound represented by the following formula (ionization potential: 5.61 eV, product name: CT-3, manufactured by Takasago Chemical Co., Ltd.) was used.

[0113] Example 14 In the same manner as in Example 1, an undercoat layer 12 and a charge generating layer 13 were formed on a conductive support 11 . Next, 25 g of compound (1) as a charge transport material, 37.5 g of polycarbonate (manufactured by Teijin Chemical Co., Ltd., product name: TS2040) and 250 g of tetrahydrofuran were added to a 900 mL soda-lime glass container, mixed, and stirred in a ball mill for 15 hours to prepare 312.5 g of a first charge transport coating liquid. The obtained coating liquid for the charge transport layer was applied onto the charge generating layer 13 by the same immersion method as in the case of forming the undercoat layer, and the obtained coating film was dried at 115°C for 1.5 hours to form a first charge transport layer with a thickness of 35 μm. Next, the coating solution for the second charge transport layer prepared in the same manner as in Example 2 was applied onto the first charge transport layer by a spray coating method, and the resulting coating film was dried at 120°C for 0.5 hours to form a 5 μm-thick second charge transport layer on the surface, thereby obtaining the photoreceptor 2 shown in Figure 1 having a charge transport layer consisting of two layers.

[0114] Example 15 A photoreceptor 1 shown in FIG. 1 was obtained in the same manner as in Example 1, except that no undercoat layer was formed.

[0115] (Example 16) In preparing the silica filler suspension of the charge transport layer coating liquid, the photoreceptor 1 shown in FIG. 1 was obtained in the same manner as in Example 1, except that the silica particles were changed to silica particles (number average primary particle size 7 nm, surface treated with dimethyldichlorosilane, manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) R976).

[0116] (Example 17) In preparing the silica filler suspension of the charge transport layer coating liquid, the photoreceptor 1 shown in FIG. 1 was obtained in the same manner as in Example 1, except that the silica particles were changed to silica particles (number average primary particle size 12 nm, surface treated with dimethyldichlorosilane, manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) R974).

[0117] (Example 18) In preparing the silica filler suspension of the charge transport layer coating liquid, the photoreceptor 1 shown in FIG. 1 was obtained in the same manner as in Example 1, except that the silica particles were changed to silica particles (number average primary particle size 12 nm, surface treated with dimethyldichlorosilane, manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) R9200).

[0118] (Example 19) A photoreceptor 1 shown in FIG. 1 was obtained in the same manner as in Example 1, except that in the preparation of the coating solution for the charge transport layer, the number of passes of the dispersion treatment using the particle dispersion device was changed from 6 passes to 1 pass.

[0119] (Example 20) A photoreceptor 1 shown in FIG. 1 was obtained in the same manner as in Example 1, except that in the preparation of the coating solution for the charge transport layer, tetrahydrofuran previously prepared as follows was used instead of 36 g of tetrahydrofuran. Soda-lime glass beads (50 g) having a diameter of 2 mm and 36 g of tetrahydrofuran were added to a 250 mL polypropylene container, and the resulting mixture was stirred in a ball mill for 1 hour to obtain tetrahydrofuran containing abrasion powder of the glass beads.

[0120] Comparative Example 1 In preparing the coating solution for the charge transport layer, the photoreceptor 1 shown in FIG. 1 was obtained in the same manner as in Example 2, except that the treatment time in the ball mill was changed from 10 hours to 30 hours.

[0121] Comparative Example 2 In preparing the silica filler suspension for the charge transport layer coating solution, the 140 mL soda lime glass container was replaced with a 250 mL polypropylene container, the silica particles were changed from 4 g to 10 g, the tetrahydrofuran from 36 g to 90 g, and the stirring time was changed from 15 to 45 hours. The charge transport material added to the obtained silica filler suspension was changed from 13.8 g to 11.5 g of compound (1), from 22.2 g to 18.5 g of polycarbonate, and from 105.8 g to 51.8 g of tetrahydrofuran. The photoreceptor 1 shown in FIG. 1 was obtained in the same manner as in Example 1. The above conditions were the same as in Example 7, except that a polypropylene container with a capacity of 250 mL was used.

[0122] Comparative Example 3 In preparing a silica filler suspension for the coating liquid for the charge transport layer, 4 g of silica particles (number average primary particle size 12 nm, surface treated with dimethyldichlorosilane, manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) R9200) were suspended in 36 g of tetrahydrofuran in a 140 mL soda-lime glass container, and the time for stirring with a stirrer (manufactured by Shibata Scientific Co., Ltd., model: M-103) and agitating blade was changed to 5 minutes, and the same procedure as in Example 1 was repeated to obtain the photoreceptor 1 shown in FIG. 1 .

[0123] [evaluation] The photoreceptors prepared in Examples 1 to 19 and Comparative Examples 1 and 2 were mounted in a unit of a digital copier (manufactured by Sharp Corporation, model: MX-B455W) modified for testing, and 300,000 images were formed to evaluate the initial sensitivity, sensitivity stability, charging stability, and cleaning ability as described below.

[0124] [Sensitivity stability, charging stability] The photoconductor surface potential in the development section, specifically the photoconductor surface potential VL(-V) of the black background when exposed to light to check the sensitivity, was measured, and the process of charging, exposing, and discharging was repeated 1 million times in an environment of 25°C temperature and 10% relative humidity, and the initial residual potential and the photoconductor surface potential after fatigue due to electrical current were measured, and the difference between these, ΔVR(V), was used to evaluate the sensitivity stability based on the following criteria and as an index of deterioration in sensitivity due to repeated use. In addition, the initial charge potential and the charge potential after current fatigue were measured, and the difference between them, ΔV0, was used as an index of charge degradation to evaluate the charge stability based on the following criteria.

[0125] <Criteria for Sensitivity Stability> A: ΔVR(V)<40 Can be used without problems in high-speed multifunction machines or printers that require high sensitivity B: 40≦ΔVR(V)<80 Can be used without problems on low to medium speed multifunction devices or printers C:80≦ΔVR(V)<140 If you have a slow, inexpensive multifunction device or printer, the density may be a little low, but it can be used without any problems. D: 140≦ΔVR(V) Poor sensitivity, low concentration, and problematic for practical use

[0126] <Criteria for determining charge stability> A: 0≦ΔV0(-V)<60 Very good, can be used without problems even in high-speed multifunction machines or printers that require high sensitivity B: 60≦ΔV0(-V)<80 Good, can be used without problems on low to medium speed multifunction devices or printers C: 80≦ΔV0(-V)<100 Fairly good. If you have a slow, inexpensive multifunction device or printer, the density may be a little low, but it is still usable. D: 100≦ΔV0(-V) Not good, problems in practical use

[0127] [Cleaning ability] The pressure (cleaning blade pressure) of the cleaning blade of the cleaning device installed in the digital multifunction printer that contacts the photoconductor is 21 gf / cm (2.06 x 10 -1 The pressure was adjusted to N / cm (initial linear pressure). A printing durability test was conducted by printing a character test chart (ISO19752) on 500,000 sheets of recording paper in a normal temperature / humidity environment of 25°C temperature / 20% relative humidity. In order to confirm the level of cleaning defects of the photoconductor after the printing durability test, the photoconductor after 500,000 images was set in a test digital copier and one sheet of A4 paper was printed with a 100% density untransferred image. Immediately after that, the image forming device was forcibly stopped and the surface of the photoconductor was visually observed and the cleaning ability (degree of defect) was evaluated based on the following criteria.

[0128] <Judgment criteria> A: No cleaning failures Can be used without problems on multifunction devices or printers that require high image quality B: 1 to 2 cleaning defects Can be used without problems on any multifunction device or printer that does not require high image quality C: 3 to 5 cleaning defects Can be used without problems with inexpensive multifunction devices or printers D: Many cleaning defects Problems in actual use

[0129] <Overall rating> Based on the results of the above evaluations, the photoreceptors were comprehensively evaluated according to the following criteria. A: A rating in all categories, very good Can be used without problems in multifunction machines or printers that require long life and high image quality B: Some items were rated B, but all items were rated B or higher Can be used without problems in any multifunction device or printer that requires long life and high image quality C: Some items were graded C, but all items were graded C or higher Can be used without problems with inexpensive multifunction devices or printers D: Any judgement includes D grade Not for actual use

[0130] The main constituent materials and physical properties of the prepared photoreceptor are shown in Table 1, and the measurement and evaluation results obtained are shown in Table 2. In Table 1, the abbreviations for the silica particles and charge transport layer materials represent parts of the product names, the resins "PC" and "PAR" represent "polycarbonate-based resin" and "polyarylate-based resin", respectively, and the layer forms "1" and "2" represent "the case where the photoreceptor does not have a surface protective layer, and the photosensitive layer (charge transport layer) contains silica particles" and "the case where the photoreceptor has a surface protective layer containing silica particles, and the photosensitive layer (charge transport layer) does not contain silica particles", respectively. In addition, the ratio of the contained elements Na and Ca is expressed as "A EB" as "A x 10 -B " means.

[0131] [Table 1]

[0132] [Table 2]

[0133] The results in Tables 1 and 2 reveal the following: (1) The photoreceptor of the present invention (Examples 1 to 20) has at least a laminated photosensitive layer in which a charge generating layer and a charge transport layer are laminated in this order on a conductive support, and the charge transport layer contains at least a charge transport material, a binder resin, and silica particles, and contains 0.1 ppm to 20 ppm of Na element and / or 0.01 ppm to 10 ppm of K element. The photoreceptor (Examples 1 to 20) has excellent printing durability and high mechanical strength, and does not cause image defects due to partial breakage of the cleaning blade or uneven image density due to wear variation. On the other hand, in the photoreceptor (Comparative Example 1) in which the charge transport layer contains Na and K elements in amounts greater than those specified in the present invention, the ten-point surface roughness Rz of the laminated photosensitive layer surface is small, and it is believed that silica is uniformly dispersed in the laminated photosensitive layer, and problems such as poor cleaning due to repeated use do not occur. However, due to the presence of a large amount of Na and K elements, the sensitivity stability and charging stability are unstable, and stable electrophotographic characteristics cannot be maintained for a long period of time. In addition, in the photoreceptor (Comparative Example 2) in which there is no contact with soda lime glass in the preparation process of the coating liquid for the charge transport layer and the charge transport layer does not contain the elements Na and K, the silica in the laminated photosensitive layer is insufficiently crushed, so that the ten-point surface roughness Rz is large, and the cleaning blade is damaged with repeated use, causing cleaning failure and image scratches, and it is not possible to maintain image quality over a long period of time.

[0134] (2) In the preparation process of the coating liquid for the charge transport layer and the second charge transport layer, when a soda-lime glass tool containing calcium oxide or magnesium oxide as well as sodium oxide or potassium oxide is used, the Ca element and Mg element in the charge transport layer and the second charge transport layer are often contained in conjunction with the Na element and K element due to contact with the glass material. When the Ca element and Mg element contents exceed 10 ppm and 8 ppm, respectively, the sensitivity stability and charging stability become slightly unstable with repeated use, as in the above (1) (Example 3). On the other hand, when the Ca element and Mg element contents are 0 or small, the silica in the laminated photosensitive layer is not sufficiently crushed, the 10-point surface roughness Rz is large, and the load on the cleaning blade becomes large with repeated use. In addition, the ratio of the Na element content to the silica particle content (Na / SF) was set to 8×10 -6 More than 2×10 -5 The ratio of the calcium element content to the silica particle content (Ca / SF) is shown below as 1×10 -7 More than 1×10 -6 By adjusting the following, sensitivity stability, charge stability, and cleaning properties are all achieved (Examples 1, 4, and 6).

[0135] (3) When the number average primary particle diameter of the silica particles exceeds 30 μm, even if the coating liquid comes into contact with soda-lime glass during the preparation process, the ten-point surface roughness Rz becomes slightly larger due to the larger silica particle diameter, and the silica aggregates in the laminated photosensitive layer become larger, so that the load on the cleaning blade tends to increase with repeated use (Example 5). On the other hand, when the number average primary particle diameter of the silica particles is less than 10 μm, the ten-point surface roughness Rz becomes too small, the contact area between the laminated photoreceptor surface and the cleaning blade increases, and the load on the cleaning blade tends to increase (Example 16). In addition, the greater the content of silica in the charge transport layer and the second charge transport layer, the better the printing durability, but the greater the ten-point surface roughness Rz and the greater the load on the cleaning blade (Example 7). In contrast, the smaller the content of silica, the lower the strength of the surface layer and the more likely image scratches and the like are to occur (Example 6).

[0136] (4) In the preparation process of the coating liquid for the charge transport layer and the coating liquid for the second charge transport layer, if the frequency of contact with a soda-lime glass tool is increased, the amount of the contained elements increases, which promotes the disintegration of silica, reduces the ten-point surface roughness Rz, and reduces the load on the cleaning blade. However, the increased amount of the contained elements tends to make the sensitivity stability and charging stability unstable with repeated use (Example 8). In addition, when the ten-point surface roughness Rz of the charge transport layer increases, the load on the cleaning blade increases, and although it can be used without problems in inexpensive multifunction machines or printers, there is a high possibility that the life of the photoconductor will be shortened (Examples 9, 10, 18, and 19).

[0137] (5) A photoconductor using a resin having a polyarylate skeleton as the binder resin in the charge transport layer is less susceptible to deterioration of the photoconductor surface due to repeated use than a photoconductor using a polycarbonate resin, and can reduce the load on the cleaning blade, but the sensitivity stability due to repeated use tends to be slightly inferior (see Examples 6 and 11).

[0138] (6) When the ionization potential of the charge transport material is 5.55 eV or less, the sensitivity stability during repeated use is good, and in particular, when the charge transport material is Compound 1 (a stilbene derivative), stable sensitivity characteristics can be maintained for a long period of time (see Examples 1, 12, and 13). On the other hand, when the ionization potential is less than 5.4 eV, Oxidizing gases The ionization potential of the charge transport material is optimally set to 5.4 eV or more and 5.55 eV or less, because the material is significantly affected by chemical deterioration, the risk of image defects increases, and care must be taken from the machine side, such as by installing an oxidizing gas exhaust mechanism within the actual machine.

[0139] (7) By providing an undercoat layer between the conductive support and the laminated photosensitive layer, the charging stability during repeated use can be improved (see Examples 1 and 15). [Explanation of symbols]

[0140] 1, 2 Electrophotographic photoreceptor 11 Conductive support 12 Undercoat layer (middle layer) 13 Charge generation layer 14 Charge transport layer 15 First charge transport layer 16 Second charge transport layer 17 Laminated photosensitive layer 18 Silica particles

[0141] 31 Exposure means (semiconductor laser) 32 Charging means (charger) 33 Developing means (developer) 33a Developing roller 33b Casing 34 Transfer means (transfer charger) 35 Fixing means (fixing device) 35a Heating roller 35b Pressure roller 36 Cleaning means (cleaner) 36a cleaning blade 36b Recovery casing 37 Separation means 38 Housing 41, 42 arrow mark 44 Rotation axis 51 Recording media (recording paper or transfer paper) 100 Image forming apparatus (laser printer)

Claims

1. The electrophotographic recording medium comprises at least a laminated photosensitive layer in which a charge generating layer and a charge transport layer are laminated in this order on a conductive support, the charge transport layer contains at least a charge transport material, a binder resin and silica particles, and contains 0.1 ppm to 4.1 ppm of Na element and 0.01 ppm to 0.06 ppm of K element, which are wear powder derived from a soda-lime glass material.

2. 2. The electrophotographic photoreceptor according to claim 1, wherein the charge transport layer contains 0.01 ppm to 10 ppm of Ca element and / or 0.01 ppm to 8 ppm of Mg element.

3. 3. The electrophotographic photoreceptor according to claim 1, wherein the silica particles have a number average primary particle diameter of 10 nm to 30 nm, and the content of the silica particles in the charge transport layer is 7% by weight to 25% by weight.

4. The mass ratio [Na / SF] of the content [Na] of Na element to the content [SF] of silica particles in the charge transport layer is 8×10 -6 Above 2 x 10 -5 4. The electrophotographic photoreceptor according to claim 1, wherein:

5. The mass ratio [Ca / SF] of the content [Ca] of Ca element to the content [SF] of silica particles in the charge transport layer is 1×10 -7 Above 1 x 10 -6 5. The electrophotographic photoreceptor according to claim 2, wherein:

6. 6. The electrophotographic photoreceptor according to claim 1, wherein the charge transport material has an ionization potential of 5.4 eV or more and 5.55 eV or less.

7. The charge transport material is represented by the general formula (I): 【Chemistry 1】 (In the formula, R 1 , R 2 , R 5 and R 6 are the same or different and each is an alkyl group, an alkoxy group, an aryl group, an aralkyl group, or a halogen atom; m, n, p, and q are the same or different and each is an integer of 0 to 3; R 3 and R 4 are the same or different and each is a hydrogen atom or an alkyl group.

7. The electrophotographic photoreceptor according to claim 1, wherein the stilbene derivative is represented by the formula:

8. 8. The electrophotographic photoreceptor according to claim 1, wherein the charge transport layer has a ten-point surface roughness Rz of 0.1 μm or more and 1.0 μm or less, as defined in JIS-B-0601 (1994).

9. 9. The electrophotographic photoreceptor according to claim 1, wherein the binder resin is a resin having a polycarbonate Z skeleton or a polyarylate skeleton.

10. 10. The electrophotographic photoreceptor according to claim 1, wherein the charge transport layer is a first charge transport layer and a second charge transport layer which are sequentially laminated on the charge generating layer, the first charge transport layer containing a charge transport material and a binder resin, and the second charge transport layer containing a charge transport material, a binder resin, and silica particles.

11. an image forming apparatus comprising at least the electrophotographic photoreceptor according to any one of claims 1 to 10, a charging means for charging the electrophotographic photoreceptor, an exposure means for exposing the charged electrophotographic photoreceptor to light to form an electrostatic latent image, a developing means for developing the electrostatic latent image formed by exposure to form a toner image, a transfer means for transferring the toner image formed by development onto a recording medium, a fixing means for fixing the transferred toner image on the recording medium to form an image, a cleaning means for removing and recovering toner remaining on the electrophotographic photoreceptor, and a discharging means for discharging surface charge remaining on the electrophotographic photoreceptor.

12. A method for producing an electrophotographic photoreceptor according to any one of claims 1 to 10, A method for manufacturing an electrophotographic photoreceptor, comprising the step of forming a charge transport layer using a coating liquid for a charge transport layer, the coating liquid containing at least a charge transport material, a binder resin and silica particles, and containing, based on the solid content, 0.1 ppm to 4.1 ppm of Na element and 0.01 ppm to 0.06 ppm of K element, the abrasion powder being derived from a soda-lime glass material.

13. A method for producing an electrophotographic photoreceptor comprising at least a laminated photosensitive layer having a charge generating layer and a charge transport layer laminated in this order on a conductive support, the charge transport layer containing at least a charge transport material, a binder resin and silica particles, and containing 0.1 ppm or more and 4.1 ppm or less of Na element and 0.01 ppm or more and 0.06 ppm or less of K element, which are wear powder derived from a soda-lime glass material, 1. A method for producing an electrophotographic photoreceptor, comprising the steps of: suspending silica particles in a solvent in a soda-lime glass container and stirring the mixture; adding a charge transport material, a binder resin and a solvent to the suspension obtained, mixing the mixture, and stirring the mixture; and dispersing the mixture obtained to prepare a coating liquid for a charge transport layer, and applying the coating liquid for the charge transport layer obtained on a charge generating layer to form a charge transport layer.

14. A coating liquid for a charge transport layer used in the method for producing an electrophotographic photoreceptor according to claim 12 or 13, A coating liquid for a charge transport layer, comprising at least a charge transport material, a binder resin and silica particles, and containing, based on the solid content, 0.1 ppm to 4.1 ppm of Na element and 0.01 ppm to 0.06 ppm of K element, which are abrasion powder derived from a soda-lime glass material.

Citation Information

Patent Citations

  • Production of coating liquid for producing electrophotographic photoreceptor and electrophotographic photoreceptor using the same

    JP1997211873A

  • Production of silica dispersion

    JP1998310416A

  • Electrophotographic photoreceptor, electrophotographic process cartridge and electrophotographic device

    JP2001066800A

  • Method for producing electrophotographic photoreceptor, electrophotographic photoreceptor using the method, image forming method and device using the photoreceptor, and process cartridge

    JP2001142243A

  • Organic photoreceptor, method and apparatus for image formation, and process cartridge

    JP2004004454A